Rechargeable Soft‐Matter EGaIn‐MnO2 Battery for Stretchable Electronics - Liu, Dongye; Su, Laisuo; Liao, Jiahe; Reeja‐Jayan, B.; Majidi, Carmel (Advanced energy materials, 2019)
A rechargeable, stretchable battery composed of a liquid metal alloy (eutectic gallium‐indium; EGaIn) anode, a carbon paste, and MnO2 slurry cathode, an alkaline electrolytic hydrogel, and a soft elastomeric package is presented. The battery can stably cycle within a voltage range of 1.40–1.86 V at 1 mA cm−2 while being subject to 100% tensile strain. This is accomplished through a mechanism that involves reversible stripping and plating of gallium along with MnO2 chemical conversion. Moreover, a technique to increase the contact area between the EGaIn anode and hydrogel interface using CaCl2 additives, which reduces polarization and therefore reduces the effective current density, leading to higher discharge plateaus and lower charge plateaus. Relative to previous attempts at energy storage with liquid metal, the EGaIn‐MnO2 battery presented here shows an exceptional areal specific capacity (≈3.8 mAh cm−2) and robust, stable rechargeability over >100 charging cycles. The battery is also stable under bending, with negligible change in electrochemical properties when bent to a 2 mm radius of curvature. Batteries embedded within a wearable elastomeric sleeve can power a blue light‐emitting diode and strain‐sensing circuit. These demonstrations suggest that stretchable EGaIn‐MnO2 batteries are feasible for applications in wearable energy‐storage electronics. A stretchable, rechargeable, soft‐matter battery is achieved by combining a liquid metal alloy anode, carbon paste, MnO2 slurry cathode, and alkaline electrolytic hydrogel within a soft elastomer package. Relative to previous attempts at energy storage with liquid metal, the battery presented here shows an exceptional areal specific capacity (≈3.8 mAh cm−2) and robust, stable rechargeability over >100 charging cycles.